2017
DOI: 10.1016/j.athoracsur.2017.04.053
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Cerebral Perfusion Disturbances During Transcatheter Aortic Valve Replacement

Abstract: Cerebral oximetry reacted promptly to rapid ventricular pacing with significant desaturation and hyperemia a common occurrence. However, no association between this intraoperative insult and objective neurologic injury was detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…Seven studies reported IHPOD according to the CAM, for a total of 682 patients (Figure ) . The pooled estimate rate of CAM‐defined IHPOD was 13.5% (95% CI=4.9–22.1%), with evidence of high interstudy heterogeneity (Q = 151; I = 96%; p heterogeneity < .001).…”
Section: Resultsmentioning
confidence: 77%
See 4 more Smart Citations
“…Seven studies reported IHPOD according to the CAM, for a total of 682 patients (Figure ) . The pooled estimate rate of CAM‐defined IHPOD was 13.5% (95% CI=4.9–22.1%), with evidence of high interstudy heterogeneity (Q = 151; I = 96%; p heterogeneity < .001).…”
Section: Resultsmentioning
confidence: 77%
“…The majority of participants included in our meta‐analysis were derived from 2 large prospective registries, with the lack of information regarding delirium diagnostic criteria and timing of the delirium screening . Interestingly, while these 2 large studies reported lower incidence of IHPOD after TAVR (e.g., 3.8% and 4.6%), small studies included in our analysis report higher incidence of IHPOD after TAVR . Several participant‐ and procedural‐related factors, including age at admission, comorbid condition, TAVR access, and hospital complication rate, could explain the differences in the incidence of IHPOD between these studies.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations